Vaccination and Infection as Causative Factors in Japanese Patients With Rasmussen Syndrome: Molecular Mimicry and HLA Class I - Yukitoshi Takahashi; Kazumi Matsuda; Yuko Kubota; Jiro Shimomura; Etsuko Yamasaki; Tatsuya Kudo; Katsuyuki Fukushima; Hitoshi Osaka; Noriyuki Akasaka; Atsushi Imamura; Shinji Yamada; Naomi Kondo; et al. (Clinical and Developmental Immunology)
Rasmussen syndrome is an intractable epilepsy with a putative causal relation with cellular and humoral autoimmunity. Almost half of the patients have some preceding causative factors, with infections found in 38.2%, vaccinations in 5.9% and head trauma in 8.9% of Japanese patients. In a patient with seizure onset after influenza A infections, cross-reaction of the patient's lymphocytes with GluRε2 and influenza vaccine components was demonstrated by lymphocyte stimulation test. Database analyses revealed that influenza A virus hemagglutinin and GluRε2 molecules contain peptides with the patient's HLA class I binding motif (HLA ࢤ A*0201). The relative risks of HLA class I genotypes for Rasmussen syndrome are 6.1 (A*2402), 6.4 (A*0201), 6.3 (A*2601) and 11.4 (B*4601). The relative risks of HLA class I-A and B haplotypes are infinity (A*2601+B*5401), 21.1 (A*2402+B*1501), 13.3 (A*2402+B*4801) and 5.1 (A*2402+B*5201). Some alleles and haplotypes of HLA class I may be the risk factors in Japanese patients. Cross-reactivity of cytotoxic T lymphocytes may contribute to the processes leading from infection to the involvement of CNS.